Perencanaan Kurikulum Muatan Lokal dalam Mengembangkan Karakter Siswa - Denden Sumarlin; Suharyanto S Soro (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The national curriculum is considered not fully able to accommodate the needs of local values ​​and the unique character of students, so schools have an important role in designing a contextual curriculum. Alfath IT High School in Sukabumi City, as an Islamic and technology-based school, is a relevant locus for studying the practice of Local Content curriculum planning in developing student character. This study aims to describe and analyze the Local Content curriculum planning process, identify the types of Local Content developed, and explain its contribution to the formation of religious, independent, and technologically-minded characters. The research method used is a qualitative case study approach, through in-depth interviews, observations, and documentation studies. The results show that Local Content curriculum planning is carried out systematically, collaboratively, and based on an analysis of student needs and the school's vision. The planning process includes setting character objectives, selecting contextual materials, practice-based learning strategies, and ongoing evaluation. The implications of this study confirm that mature Local Content curriculum planning can be an important foundation in strengthening character education in schools, while also providing practical references for curriculum developers and educational policy makers.